2019
DOI: 10.1016/j.jsps.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring healthcare professionals’ perceptions of medication errors in an adult oncology department in Saudi Arabia: A qualitative study

Abstract: ObjectiveAdverse events which result from medication errors are considered to be one of the most frequently encountered patient safety issues in clinical settings. We undertook a qualitative investigation to identify and explore factors relating to medication error in an adult oncology department in Saudi Arabia from the perspective of healthcare professionals.MethodsThis was a qualitative study conducted in an adult oncology department in Saudi Arabia. After obtaining required ethical approvals and written co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Using of focus group discussion offered opportunity to generate data through discussion among participants to share their knowledge and opinions to obtain solutions to minimize medication errors in the department (Hays and Singh, 2011). The discussion topic guides were informed by findings of our two previous studies (Alharbi et al, 2018, Alharbi et al, 2019) and related literature (Al-Dhawailie, 2011, Almutary and Lewis, 2012, Aljadhey et al, 2014). Questions included, which area we should focus on for minimizing medication errors in the department?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using of focus group discussion offered opportunity to generate data through discussion among participants to share their knowledge and opinions to obtain solutions to minimize medication errors in the department (Hays and Singh, 2011). The discussion topic guides were informed by findings of our two previous studies (Alharbi et al, 2018, Alharbi et al, 2019) and related literature (Al-Dhawailie, 2011, Almutary and Lewis, 2012, Aljadhey et al, 2014). Questions included, which area we should focus on for minimizing medication errors in the department?…”
Section: Methodsmentioning
confidence: 99%
“…Each focus group meeting was facilitated by the first author (WH) and started with 10 min presentation to introduce causes of medication errors identified in the two previous studies (Alharbi et al, 2018, Alharbi et al, 2019). Following the presentation, discussion about strategies to minimize medication errors was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the findings from the study of Gorgich and his colleagues suggested that common MEs in medication prescription can affect incorrect medication concentration, incorrect-time medication administration, medication overdose, and incorrect way of medication administration [18]. However, there is some evidence to suggest that MEs by nursing professionals are high, yet the rate of error reporting among them is low [19]. According to a recent study by Marznaki et al, the rate of MEs in nursing staff was reportedly 50%, and the most common type of MEs was forgetting medication prescriptions and incorrect dosage [20].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Medication safety behaviours among health care providers likely have considerable influence on minimizing medication safety threats and the implementation of well-evidenced interventions (Parry, Barriball, & While, 2015). Previous research suggests that the behaviour of staff involved in medication therapy is closely connected to medication safety (Alharbi, Cleland, & Morrison, 2019). To improve quality of care and safety, a systemic approach is required to take staff behavioural changes into consideration.…”
Section: Introductionmentioning
confidence: 99%